2018
DOI: 10.18203/2320-1770.ijrcog20183294
|View full text |Cite
|
Sign up to set email alerts
|

Gamma glutamyl transferase and lactate dehydrogenase as biochemical markers of severity of preeclampsia among Sudanese pregnant women

Abstract: Background: Preeclampsia is a disorder of widespread vascular endothelial malfunction and vasospasm that occurs after 20 weeks' gestation and can present as late as 4-6 weeks post-partum. Pre-eclampsia is a syndrome with multiple aetiologies which has made it difficult to develop adequate screening tests and treatments. Objective of this study to assess the level of gamma glutamyl transferase and lactate dehydrogenase as biochemical markers of severity of preeclampsia in Sudanese pregnant women.Methods: This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…Another research undertaken in India reported mean serum level of LDH to be 513.37 ± 203.44 and 261 ± 78.47 in preeclamptic and healthy controls, respectively. In addition, a study done in Ethiopia reported mean level of serum LDH in preeclamptic study groups to be 353 ± 132.8 which was slightly lower than the finding of the present study (8,24,25). This observed discrepancy might possibly be due to the lowering effects of antihypertensive drugs, which were being taken by some of our study subjects.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Another research undertaken in India reported mean serum level of LDH to be 513.37 ± 203.44 and 261 ± 78.47 in preeclamptic and healthy controls, respectively. In addition, a study done in Ethiopia reported mean level of serum LDH in preeclamptic study groups to be 353 ± 132.8 which was slightly lower than the finding of the present study (8,24,25). This observed discrepancy might possibly be due to the lowering effects of antihypertensive drugs, which were being taken by some of our study subjects.…”
Section: Discussioncontrasting
confidence: 89%
“…In our study, the AUC for serum LDH, measuring its overall performance to predict development of preeclampsia, was 0.963, and its optimal cut-off point was found to be 376.5 U/L having a sensitivity and specificity of 87.5 and 90.8%, respectively. This finding was higher than a research conducted in India on similar subjects which found AUC for serum LDH to be 0.813, with sensitivity and specificity of 83.8 and 58%, respectively, at 250 U/L as cut-off value, and a study done in Iran which reported AUC for serum LDH 0.805 at an optimal cut-off point of 336 U/L with high sensitivity and moderate specificity (89.62 and 59.3% respectively) (15,25). On the contrary, a study done by Khalil et al in Saudi Arabia reported sensitivity of LDH to identify severe preeclampsia as 100%.…”
Section: Discussionmentioning
confidence: 89%
“…Also, serum activities of CT, TB, LDH, and GGT correlate with liver function and elevated activities are observed in Table 2. Effect of cimetidine on liver tissue biochemical indices of methotrexate-treated rats hepatic disorders [31]. The serum and liver activities of CT, CB, AST, GGT, ALT, LDH, and ALP were high in rats treated with MTX.…”
Section: Discussionmentioning
confidence: 96%